Gray Abbey, Co. Down - Burgess, James Howard; Hall, S. C., Mrs., 1800-1881 (1840)
View of the ruins of Gray (Grey) Abbey.
Title inscribed l.c. on sheet.
Attributed to James Howard Burgess.
Catalogue of Irish Topographical Prints and Original Drawings / Rosalind M. Elmes ; New edition revised and enlarged by Michael Hewson - Dublin : Malton Press, 1975
Ireland: its scenery, character, &c / Mr. & Mrs. S. C. Hall - London: How and Parsons, 1841-43.
Keywords: Abbeys -- Northern Ireland -- Down (County) -- 1830-1840; Down (Northern Ireland : County); Pencil drawings -- Irish -- 1830-1840.